Implementing data analytics and architectures for next generation wireless communications - Bhatt, Chintan M. 1988-; Kumar, Neeraj; Bashir, Ali Kashif 1982-; Alazab, Mamoun 1980- (IGI Global, 2021)
"This book covers the existing and emerging theoretical and practical challenges in the design, development and implementation of big data algorithms, protocols, architectures, and applications for next-generation wireless communications and their applications in smart cities"--
Includes bibliographical references and index
Chapter 1. Blockchain and green networking analytics in 5G networks and beyond -- Chapter 2. Improving water efficiency in the beverage industry with the Internet of things -- Chapter 3. Network intrusion detection using linear and ensemble ML modeling -- Chapter 4. 5g in healthcare: features, advantages, limitations, and applications -- Chapter 5. High-speed connectivity: potential impact on the quality of life -- Chapter 6. A rabin cryptosystem-based lightweight authentication protocol and session key-generation scheme for IoT deployment: authentication in IoT -- Chapter 7. Multi-keyword searchable encryption for e-health system with multiple data writers and readers -- Chapter 8. A comparative study on symmetric and asymmetric key encryption techniques -- Chapter 9. Demystifying multi-tier cost model for scheduling in fog communication networks -- Chapter 10. Analysis of bluetooth versions (4.0, 4.2, 5, 5.1, and 5.2) for IoT applications -- Chapter 11. Evalutation of turbo decoder performance through software reference model. - Mode of access: World Wide Web
Keywords: Artificial intelligence / fast; Big data / fast; Computer network architectures / fast; Internet of things / fast; Wireless communication systems / fast; Computer network architectures; Big data; Wireless communication systems; Internet of things; Artificial intelligence